The Textile and Clothing Industry in the Danube Region Countries - Comparative Advantages - Ignjatijević, Svetlana D; Raičević, Vuk (Industrija, 2016)
The subject of this study is the analysis of comparative advantages of international export in the TC (textile and clothing) industry of the Danube region countries with a special focus on Serbia. The aim of this study is to analyze the comparative advantage and suggest possible economic and legal measures to strengthen export. This study observed export per capita and participation of TC industry export, and measured the comparative advantage and specialization of the Danube region countries in the period between 2005 and 2013. In the course of research, we used the Balassa (RCA) and Lafay (LFI) indexes of comparative advantage, and the GL index and RUV index of horizontal and vertical specialization in intra-industry exchange. The research has revealed positive comparative advantage in the export of the textile industry in the Czech Republic, Germany and Slovenia. In the clothing industry export, positive comparative advantage was revealed in the cases of: Bulgaria, Hungary, Moldova, Romania, Slovakia and Serbia. The research has shown a positive comparative advantage of the TC industry sector in Serbia. The results of our research into the TC industry reveal the existence of correlation between comparative advantage and intra-industry specialization in international trade.
Keywords: Textiles; Industries; Export; Comparative advantage; Clothing industry; Clothing